Identification of Diction, Figures of Speech, Imagery, and Musicality in the Lyrics of the Song افرحوا النور أتانا from Noam Chomsky’s Stylistic Perspective - Dewantara, Muhammad Fajar Tubagus; Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to identify and analyze diction, figurative language, imagery, and musicality found in the song lyrics افرحوا النور أتانا from the perspective of Noam Chomsky’s stylistics. The song lyrics represent one of the Arabic literary works rich in aesthetic value and linguistic beauty, making them worthy of in-depth examination using a stylistic approach. This study employs a qualitative research method with a descriptive-analytical approach, namely describing and analyzing data systematically based on the stylistic theory proposed by Noam Chomsky, particularly the concepts of deep structure and surface structure, as well as linguistic creativity. The data source in this study is the song lyrics of افرحوا النور أتانا, analyzed textually. Data collection techniques were carried out through library research and documentation, while data analysis techniques employed reading, note-taking, and interpretation methods. The results of the study indicate that the song lyrics of افرحوا النور أتانا contain beautiful diction filled with symbolic meaning, diverse figurative language such as metaphor and personification, strong imagery, particularly visual and auditory imagery, as well as musicality reflected through rhyme, rhythm, and harmonious sound repetition. All of these stylistic elements form a creative and aesthetic linguistic expression, consistent with Chomsky’s view that humans possess the ability to generate unlimited new expressions from their existing language system.